GOLDEN AGE : METODE PEMBELAJARAN YANG TEPAT DAN ALAT PERAGA EDUKATIF (APE) UNTUK MENDORONG KUALITAS ANAK USIA EMAS PAUD DAN TK “HARAPAN” DI DUSUN BAJULMATI DESA GAJAHREJO KEC. GEDANGAN KABUPATEN MALANG - Enggar Nursasi; Siti Munfaqiroh (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Activities that support the development of children in the golden age (1-5 years) can be done both at home and in PAUD and TK schools. Child growth at this time is fast. If the child can do the task given according to his age, then the chances of his success in carrying out other tasks according to the child's age development in the following year will be greater. The media used in children's cognitive development in early childhood and kindergarten is basically a safe and enjoyable medium. The teacher can use the media as an intermediary in delivering. An activity favored by PAUD and TK children is playing activities. Almost all playing activities actually use educational games (APE).